Reasons, inescapability and persuasion - Sinclair, Neil (Springer, 2016)
This paper outlines a new metasemantic theory of moral reason statements, focused on explaining how the reasons thus stated can be inescapable. The motivation for the theory is in part that it can explain this and other phenomena concerning moral reasons. The account also suggests a general recipe for explanations of conceptual features of moral reason statements.